Genome-wide association study identifies two risk loci for tuberculosis in Han Chinese - Ruijuan Zheng (Nature Portfolio, 2018)
Genetic risk loci for tuberculosis (TB) have so far been identified in African and Russian populations. Here, the authors perform a three-stage GWAS for TB in Han Chinese populations and find two risk loci near ESRRB and TGM6 and further demonstrate that tgm6 protects mice from Mtb infection.